CuI/PPA-Catalyzed Synthesis of Novel Sulfur-Containing Quinoline Isosteres: In Silico and DFT Analyses - Kolandaivel Prabha; Satheeshkumar Rajendran; Gamze Tüzün; Kailasam Saravana Mani; Koray Sayin (Heteroatom Chemistry)
The promising approach toward the synthesis of novel sulfur-based quinoline and benzoquinoline isostere molecules. The condensation reaction involves 4-chloro-2,8-dimethylquinolines or 4-chloro-2-methylbenzo[h]quinoline and corresponding o-thiosalicylic acid and 2-mercaptonicotinic acid, either in ethanol (as a solvent) or under solvent-free (neat) conditions. This results in the formation of an intermediate, which yields significantly better results when using neat solvent-free conditions. The intermediates then undergo cyclization using polyphosphoric acid (PPA). Notably, the sulfur-based quinoline and benzoquinoline isosteres are prepared through a highly efficient one-pot methodology using CuI/Cs2CO3/DMSO conditions, which yields higher than the PPA condition through a step-by-step method. The synthesized novel sulfur-containing isosteres are further analyzed through quantum chemical calculations of the frontier molecular orbitals (FMOs) and molecular electrostatic potential (MEP) using the M06-2X method with a 6-311 + G (d, p) basis set in water. Additionally, in silico analyses are performed in detail to predict the potential biological activity of the synthesized molecules through molecular docking and MM-GBSA analysis against the CDK8/CycC complex. Furthermore, ADME parameters have been analyzed, and all the final cyclized molecules show the most promising drug-like properties, inspiring further research in medicinal chemistry.